Factors Influencing Performance of Employees at Department of Police and Firefighters - Adrizal Efendi; Muhammad Iqbal; Vicky Afriyan Nugraha; Suhelmi Helia (International Journal of Islamic Business and Management Review, 2025)
This study aims to examine the effects of: Role conflict on the performance of employees of the Satpol PP and Fire Department of Kerinci Regency. Workload on the performance of employees of the Satpol PP and Fire Department of Kerinci Regency. Work stress on the performance of employees of the Satpol PP and Fire Department of Kerinci Regency. Role conflict, workload, and work stress jointly on the performance of employees of the Satpol PP and Fire Department of Kerinci Regency. The population for this study comprised all employees of the Civil Service Police Unit and Fire Department of Kerinci Regency, totaling 44 individuals. The sampling technique employed was total sampling (i.e., the entire population), resulting in a sample size of 42 employees. The results of the study indicate that: Role conflict has a negative effect on the performance of Satpol PP and Fire Department employees of Kerinci Regency. Workload has a negative effect on the performance of Satpol PP and Fire Department employees of Kerinci Regency. Work stress has a negative effect on the performance of Satpol PP and Fire Department employees of Kerinci Regency. Together, role conflict, workload, and work stress significantly affect the performance of Satpol PP and Fire Department employees of Kerinci Regency. Based on the conclusions above, the researcher offers the following suggestions: Clear Role Definition Management needs to clarify job descriptions and responsibilities for each employee to avoid overlapping duties. Workload Management Workload should be adjusted according to the capacity and competence of employees. Regular evaluation of workload is essential to prevent excessive fatigue. Work Stress Management Psychological support programs are needed, such as regular counseling, stress management training, and the creation of a comfortable and communicative work environment. Human Resource Development and Regular Training Enhancing employee capacity through regular training will help them manage work pressure and improve the quality of public service delivery. Employee Performance, Role Conflict, Workload, Work Stress